Wildcat [videorecording (DVD)] - Hawke, Ethan, 1970-; Gaines, Shelby; Gaines, Shelby; Hawke, Maya, 1998-; Casal, Rafael, 1985-; Ettinger, Philip; Hoffman, Cooper, 2003-; Zahn, Steve, 1968-; Linney, Laura; Cosens, Steve; Gaines, Latham, 1964-; O'Connor, Flannery (Oscilloscope Laboratories, 2025)
As 24 year-old Flannery O'Connor is writing her first novel, she is already pondering huge questions of morality and humanity when she is diagnosed with lupus--the disease her father died from when she was a child. She decides to visit her mother despite their strained relationship, but her health crisis invokes a crisis of faith, and the lines between reality, imagination, and religion begin to blur.